A 'smart' bottom-up whole-systems approach to a zero-carbon built environment. Issue 5 (4th July 2018) - Jones, Phil
ABSTRACT: Since the energy crisis of the mid and late 1970s, society has been aware of the need for a built environment that uses less fossil fuel energy. Although the built environment accounts for a large proportion of global fossil fuel use, it may be argued that the energy and buildings agenda is not being addressed at the depth or scale needed to meet global and national CO2 emission-reduction targets. Most actions to reduce energy use in the built environment have mainly used a 'top-down' decision-making approach, from government and industry, with little end-user engagement. Greenhouse gas emission-reduction targets will not be met without providing the technological and socio-economic pathways for achieving them. The paper is divided into three parts. Firstly, it discusses the need to reduce fossil fuel use and the apparent failure to transition policy goals and aims into practice. Secondly, top-down and bottom-up approaches are reviewed, advocating a greater emphasis on a 'whole-system' bottom-up approach in delivering multiple benefit solutions. Thirdly, the concept of 'smart' is considered in relation to bottom up with its implementation at a regional scale.